Ewolucja koncepcji ekonomicznych liberałów gdańskich na łamach „Przeglądu Politycznego” w latach 1983–1989 (na tle ogólnopolskim) - Luszniewicz, Jacek (Pamięć i Sprawiedliwość, 2008)
The article presents the evolution of the economic concepts of the so-called Gdańsk liberals on the pages of the underground Przegląd Polityczny, in the period from 1983 (the beginning of publication) thru 1989 (fall of the communist regime in Poland and the temporary suspension of publication). Liberalism in the version of the democratic opposition 1976–1980 and the fi rst Solidarity (1980–1981) appeared above all in political refl ections, existing alongside often un-liberal themes (for example, appealing to collective values). Declared economic liberals found themselves in the minority, as a rule appearing individually and not moving beyond generalizations. The situation began to change after 13 December 1981. In the Solidarity underground several circles promoting economic liberalism were formed at the time. The most important turned out to be that from Gdańsk, gathered around Przegląd Polityczny. The paper, published since 1983, initially did yet not present a ‘pure’ liberal-economic orientation (also expressing support for the right-wing self-government), however, from 1985, it opened itself wide to the neo-liberal infl uence (L. von Mises, F. von Hayek, Germans of the Classical liberalism school), and with time also the pro-capitalist. The Gdańsk liberals are credited with the development of the program of universal privatization (end of 1989), as well as the founding of a national political party – the Liberal-Democratic Congress (beginning 1990).